Omni-channel Service Architectures in a Technology-based Business Network: An Empirical Insight - Reis, João Carlos Gonçalves dos (2018)
This article investigates the existing omni-channel service architectures in the front-office of technology-based business networks. It discusses the implications from the existing alignment between the networkpreferred channel with other channels and clients. The methodological approach is qualitative, exploratory in nature, and employs case study research in a large private retail bank in Portugal. It includes multiple sources of data collection for corroboration purposes, including semi-structured interviews, direct observation and institutional documents. Although we have identified four types of omnichannel architectures in a business network context, the case analysis revealed that only two of them meet all the requirements, namely: the mixed services and pure virtual services. For academics this is the first attempt to discuss a growing topic in the operations management literature. Thus, this study may also help practitioners to understand the challenges they may have to deal with an omnichannel strategy in a business network context.